The Impact of Generation Gap on Cultural Absorption in Developing High-Quality Life Work in the Era of Society 5.0 Medical Centers - Adriansyah, Agus Aan; Damayanti, Nyoman Anita; Suminar, Dewi Retno; Purnomo, Windhu; Setianto, Budhi; Lukiyono, Yauwan Tobing; Sa'adah, Nikmatus (South Eastern European Journal of Public Health, 2024)
The generational gap in the workplace often results from the age difference between senior leaders and younger employees, leading to varying work styles and potential communication misunderstandings. This issue can negatively impact teamwork. Within the context of the Society 5.0 period, this research examines how intergenerational gaps affect hospital quality of work life and cultural internalization. This research makes use of a cross-sectional design together with an analytical observational methodology. A sample size of 265 individuals was chosen using a method known as simple random selection from the community of hospital personnel that is the subject of this study. Work culture, generational differences, and work life quality are key concerns. All the Rokeach Value Survey (RVS) and the Organizational Culture Assessment Instrument (OCAI) are considered to be techniques of data collection. Chi-square testing will be used to examine the findings of the survey. The results indicate that people from Generation X have a greater degree of dedication to the process of assimilation work culture when compared to those from Generation Z and Generation Y. In contrast, Gen Z exhibits a higher standard of living in the workplace when compared to Gen X and Gen Y. Furthermore, effective cultural internalization in the workplace contributes to an enhanced employee work-life quality.